2018
DOI: 10.1590/0102-33062018abb0023
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of cell wall assembly and remodelling-related genes in Arabidopsis roots subjected to boron stress and brassinosteroid at different developmental stages

Abstract: Plant cell walls are affected by many biotic and abiotic stress conditions. The aim of this study is to determine the effects of 24-Epibrassinolide (EBL) on some cell wall-related genes in root tissue of five-and ten-week-old Arabidopsis thaliana plants exposed to boron (B) deficiency (0 µM) or toxicity (3000 µM) at the transcriptional level. Expressions of the genes that encode cellulose synthase (CESA1, CESA4, CESA6 and CESA8), cellulose synthase-like (CSLB5), expansin (EXPA5, EXPA8 and EXPA14) and cell wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In maize, some cell wall-related genes were up-regulated under salinity stress, including ZmXET1, ZmEXPA1, ZmEXPA3, ZmEXPA5, ZmEXPB1 , and ZmEXPB2 , to hydrolyze and rejoin xyloglucan molecules during cell-wall extension ( Li et al, 2014 ). When Arabidopsis plants were exposed to boron toxicity, the expression of genes that encode CesA ( CESA1, CESA4, CESA6 , and CESA8 ), and CesA-like CSLB5, EXPs ( EXPA5, EXP8 , and EXPA14 ) were reduced, while PMEs ( PME2 and PME41 ) showed a different expression pattern under boron stress and/or 24-epibrassinolide treatment ( İşkil and Surgun-Acar, 2018 ). Heat-tolerant, thermal Agrostis scabra, AsEXP1 was strongly induced by exposure to HS, is associated with thermotolerant grass germplasm ( Xu et al, 2007 ).…”
Section: Cell Wall Remodeling In Heat Responsementioning
confidence: 99%
“…In maize, some cell wall-related genes were up-regulated under salinity stress, including ZmXET1, ZmEXPA1, ZmEXPA3, ZmEXPA5, ZmEXPB1 , and ZmEXPB2 , to hydrolyze and rejoin xyloglucan molecules during cell-wall extension ( Li et al, 2014 ). When Arabidopsis plants were exposed to boron toxicity, the expression of genes that encode CesA ( CESA1, CESA4, CESA6 , and CESA8 ), and CesA-like CSLB5, EXPs ( EXPA5, EXP8 , and EXPA14 ) were reduced, while PMEs ( PME2 and PME41 ) showed a different expression pattern under boron stress and/or 24-epibrassinolide treatment ( İşkil and Surgun-Acar, 2018 ). Heat-tolerant, thermal Agrostis scabra, AsEXP1 was strongly induced by exposure to HS, is associated with thermotolerant grass germplasm ( Xu et al, 2007 ).…”
Section: Cell Wall Remodeling In Heat Responsementioning
confidence: 99%
“…In the process, cell wall remodeling (CWR) occurs in the overlying tissues to promote cell separation and the passage of expanded LRPs. The expression of CWR genes must be strictly regulated to promote the occurrence of LRs (Iskil and Surgun‐Acar, 2018). Many studies have demonstrated that auxin regulates the spatial expression of CWR genes (Lewis et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, most MaCsls were suppressed by LTs in both CS and CT banana cultivars. Similarly, boron deficiency resulted in the downregulation of CslB5 and several xyloglucan endotransglucosylase/hydrolase proteins (XTHs) in Arabidopsis roots [ 37 , 38 ]. In spinach ( Spinacia oleracea L.), CslE1 was found to be inhibited by salinity stress and a combination of salinity and cadmium stress [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant Csl genes play substantial roles in developmental processes, such as root hair formation [ 6 ], the control of organ size [ 4 ], tiller number [ 3 ] and the maintenance of adherent mucilage structure [ 1 , 2 , 5 ]. Csl genes were also reported to be involved in plant resistance/tolerance to biotic or abiotic stresses, such as salt [ 35 , 36 ], boron (B) [ 37 , 38 ] or heavy metal [ 36 , 39 ] stress, as well as pathogen infection [ 32 , 40 , 41 ]. The responses of Csl genes or hemicellulose components to low temperatures (LTs) have been reported in many plant species, including banana [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%